2021
DOI: 10.3390/molecules26092499
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Mutant DNA and mRNA by the Exosomes of Breast Cancer Cells

Abstract: Exosomes are the small vesicles that are secreted by different types of normal and tumour cells and can incorporate and transfer their cargo to the recipient cells. The main goal of the present work was to study the tumour exosomes’ ability to accumulate the parent mutant DNA or RNA transcripts with their following transfer to the surrounding cells. The experiments were performed on the MCF7 breast cancer cells that are characterized by the unique coding mutation in the PIK3CA gene. Using two independent metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In recent years, exosomal DNAs have been reported to be associated with breast cancer progression to metastases [ 89 , 90 ]. Mutant DNA and mRNA are secreted by breast tumour cells via sEVs and can be integrated into heterologous cells by sEVs; for example, phosphoinositide 3-kinase alpha (PIK3CA) mutation has been demonstrated [ 91 ]. Non-coding RNAs were considered to be only intermediate molecules and not functional.…”
Section: Exosomal Coding Rnas and Non-coding Rnas In The Pmnmentioning
confidence: 99%
“…In recent years, exosomal DNAs have been reported to be associated with breast cancer progression to metastases [ 89 , 90 ]. Mutant DNA and mRNA are secreted by breast tumour cells via sEVs and can be integrated into heterologous cells by sEVs; for example, phosphoinositide 3-kinase alpha (PIK3CA) mutation has been demonstrated [ 91 ]. Non-coding RNAs were considered to be only intermediate molecules and not functional.…”
Section: Exosomal Coding Rnas and Non-coding Rnas In The Pmnmentioning
confidence: 99%
“…In recent years, it has been reported that exosome deliver various functionlized DNA into cells via the process of exosome-endocytosis to treat cancer [ 65 69 ]. However, due to their small size, the efficiency of packaging large DNA through exosomes is very low, which limit the application of the exosome-based drug delivery system.…”
Section: Exosomes-based Nucleic Acid Delivery System For Cancer Treat...mentioning
confidence: 99%
“…According to the Exocarta database ( , accessed on 10 January 2022), exosomes are involved in the transport of more than 2838 microRNAs and 3408 mRNAs, the composition of which in microvesicles depends on the composition of parental cells and the general state of the organism. The transfer of intact mRNAs by exosomes from donor to recipient cells can participate in the exchange of phenotypic traits between cells as recipient cells receive mRNAs that are not initially expressed in them [ 12 ].…”
Section: Morphology and Content Of Exosomesmentioning
confidence: 99%
“…One of the prospective methods of early cancer diagnostics is the detection of tumor markers in biological fluids—liquid biopsy. Particularly for BC, the search for in-blood markers, such as mutations or epigenetic transformations in circulating DNA [ 8 , 9 ], circulating microRNA [ 10 , 11 , 12 ], and exosomal microRNA levels [ 13 ], and the presence of exosomal proteins [ 14 ] is ongoing. We hope that, in contrast to circulating nucleic acid analysis, comprehensive analysis of exosome proteins and microRNAs will improve the sensitivity and specificity of diagnostic systems, provide insight into the mechanisms of tumor dissemination, and enable the development of target drugs for cancer-specific therapy.…”
Section: Introductionmentioning
confidence: 99%